Ultrasound Imaging of the Articularis Genus Muscle: Implications for Ultrasound-Guided Suprapatellar Recess Injection - Wu, Wei-Ting; Chang, Ke-Vin; Naňka, Ondřej; Mezian, Kamal; Ricci, Vincenzo; Wang, Bow; Özçakar, Levent (Diagnostics, 2024)
Elucidating its dynamic interaction within the knee joint, this exploration delves into the awareness regarding the articularis genus muscle for ultrasound-guided suprapatellar recess injections. While injections into the infrapatellar recess may proceed without ultrasound guidance, we highlight concerns regarding the potential cartilage injury. In contrast, especially with ultrasound guidance, suprapatellar recess injections significantly mitigate this risk, especially in the case of collapsed recess. Originating from the distal femur and vastus intermedius, the articularis genus muscle influences the tension of the suprapatellar recess during knee motion. Sonographically identifying this muscle involves visualizing the slender linear structure of the suprapatellar recess, with guidance on differentiation from the vastus intermedius. We provide a succinct approach to ultrasound-guided suprapatellar recess injections, emphasizing needle insertion techniques and strategies to prevent fluid accumulation. In conclusion, this study serves as a concise clinician's guide, underscoring the significance of the articularis genus muscle's sonoanatomy in ultrasound-guided suprapatellar recess injections. Ultimately, procedural precision and patient safety can be advanced in this aspect.